Selective Versus Non-Selective Thoracic Fusion for Adolescent Idiopathic Scoliosis Lenke 1B/1C Curves: Multi-Center Clinical and Radiographic Analysis at 2-Year Follow-Up - Yoshinari Miyaoka; Masashi Uehara; Tomohiro Banno; Shoji Seki; Tetsuro Ohba; Hiroki Oba; Shota Ikegami; Terue Hatakenaka; Daisuke Kurogochi; Takuma Fukuzawa; Tetsuhiko Mimura; Shinji Sasao; et al. (Medicina)
Background and Objectives: This retrospective cohort study compared selective thoracic fusion (STF) and non-STF for adolescent idiopathic scoliosis (AIS) Lenke 1B/1C curves. Although STF is considered an attractive option for patients with a compensatory lumbar curve, direct clinical comparisons between STF and non-STF remain limited. Materials and Methods: AIS patients (≥2 years follow-up) undergoing posterior spinal fusion were divided into STF (57 cases) and non-STF (21 cases) groups. The correction rates of their main thoracic (MT) and thoracolumbar/lumbar (TL/L) curves, coronal balance, and SRS-22r scores were statistically compared. Results: Two years after the operation, while MT curve correction and coronal balance showed no significant differences, TL/L curve correction was significantly higher in the non-STF group. In contrast, the STF group had a significantly higher SRS-22r function score, with comparable results for self-image and satisfaction. Conclusions: Both STF and non-STF present distinct characteristics that should be considered to optimize surgical decision-making.